Sistem pengendalian internal berbasis COSO untuk pencegahan fraud di Rumah Sakit Muhammadiyah / Aisyiyah Wilayah Jawa Tengah - Astuti, Pudji; Maghfiroh, Siti; Ramadhanti, Wita Ramadhanti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The importance of equitable health for all people is part of national development that must be considered by the government. With a high level of health, it will increase strong human resources. The government issued Law No. 23 of 1992 concerning health, which states that every Republic of Indonesia has the right to obtain the highest degree of health and needs to be included in government health efforts. The purpose of this study was to find out how the Internal System of the Muhammadiyah / Aisyiyah Hospital in the Central Region could prevent fraud. The method used is qualitative with descriptive type. The results of this study indicate that the Internal Control System is running rffectively as indicated that all Muhammadiyah / Aisyiyah hospitals in the Central Java region have been fully accredited, which reflects that the Internal Control System is running well fraud will be prevented as early as passible so that the objectives of Good Corporate Governance ( GOG ) can be achieved.